Society/Community: Relations of Adaptation/Resistance to the Project Contained in Modernity: Lessons Learned from the Experience in Popular/Communitary/Rural Education in Corral de Piedra, Nicoya (2011-2013) - Herra Castro, Ernesto (2015)
This article discusses the logic and the vertical domain order contained in modernity/coloniality and its concrete expression in the Costa Rican educational dynamics. It shows the tension between formal education and the possibilities of freedom and disconnection with the order imposed by modernity that seeks and promotes popular education. This is done based on the experience of the project called “Critical literacy in school culture: society and human rights" in Guanacaste.